The role of salient beliefs influence on Malaysian academics’ intention to publish in indexed journals - Hosen, Mosharrof; Chong, Yee-Lee; Lau, Lin-Sea (Malaysian Journal of Library and Information Science, 2021)
To qualify in world top universities rankings, various incentives have been provided by private universities in Malaysia to improve one of the quantifiable performance indicators: imparting, sharing and transferring knowledge through research publication which, however, is still embryonic stage. To develop effective tactical strategies, the full version of Theory of Planned Behaviour (TPB) including salient beliefs that can cause the academics to form specific reactions towards attitude, subjective norm, and perceived behavioural control constructs need to be elicited and analysed through preliminary study that nevertheless is limited in the literature. To fill up this important research gap, this paper intends (1) to increase the understanding of what the full-version of TPB constructs measure; (2) to discuss the procedure for eliciting the salient beliefs; and (3) to understand how data on salient beliefs are to be analysed. The results revealed a number of new insightful behavioural, normative and control beliefs that go beyond the current understanding of the theory of planned behaviour. The findings of the study contribute to developing appropriate behavioural intervention programs to enhance academics’ intention to publish articles in highly reputable indexed journals. Overall, this article intends to provide useful indications to researchers to understand the importance of applying the full version of the TPB, and how a more structured method can be used to elicit and measure the descriptors of salient beliefs.